The Philippines’ Two Private Sectors - Mark R. Yee , Karol (International Higher Education, 2020)
Philippine higher education has one of the world's largest and longest standing private sector—in fact, two private sectors, for-profit and nonprofit. In the face of the continued expansion of the public sector, the abolition of tuition fees in the public sector, and the opening up of the higher education market to foreign players, private institutions grapple with their changing roles. This article discusses the evolution of the private sectors, contrasting them to the public sector and to each other.